2022
DOI: 10.3390/su14106153
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Prediction Model and Analysis in the Yellow River Basin Based on a Machine Learning Method

Abstract: Excessive carbon emissions seriously threaten the sustainable development of society and the environment and have attracted the attention of the international community. The Yellow River Basin is an important ecological barrier and economic development zone in China. Studying the influencing factors of carbon emissions in the Yellow River Basin is of great significance to help China achieve carbon peaking. In this study, quadratic assignment procedure regression analysis was used to analyze the factors influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Promoting coordinated regional development is one of China's major national strategies in the new era. Although many scholars have found spatial heterogeneity in carbon emissions in the YRB [33,[52][53][54], they have failed to quantify the sources of regional differences and their convergence characteristics. In this paper, the regional differences and convergence characteristics of carbon emission intensity in the YRB are analyzed in detail by using the Markov chain, Dagum Gini coefficient, and variation coefficient method.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting coordinated regional development is one of China's major national strategies in the new era. Although many scholars have found spatial heterogeneity in carbon emissions in the YRB [33,[52][53][54], they have failed to quantify the sources of regional differences and their convergence characteristics. In this paper, the regional differences and convergence characteristics of carbon emission intensity in the YRB are analyzed in detail by using the Markov chain, Dagum Gini coefficient, and variation coefficient method.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of scholars use machine learning methods to solve the prediction problem of complex data. Zhao et al [1] found that machine learning has become a hot topic in the field of complex data prediction. They believe that models such as back propagation neural networks, support vector machines, long and short-term memory neural networks, random forests and extreme learning machines can such as effectively complete the prediction of complex data such as carbon emissions.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, machine learning models have also been increasingly applied to the study of CO2 emissions. However, while many such studies focus solely on prediction, such as emission size, emission intensity, and emission trend, they also require the selection of influential factors, which are often either derived from existing literature or arbitrarily designated (Li et al 2018, Zhao et al 2022a. Fewer studies have applied explainable methods to explore the relationships between input features and CO2 emissions.…”
Section: Introductionmentioning
confidence: 99%